Institutional and Social Pressure in Violating the Police Code of Ethics - Wirawan, Hendra; Koesbardiati , Toetik; Sutinah (Jurnal Ilmu Kepolisian, 2024)
Institutional and social pressures on police officers often lead to violations of the code of ethics. This study aims to determine how institutional and social pressures can encourage ethical violations committed by police officers. This research is a qualitative study based on in-depth interviews with seven informants to explore and precisely describe the social phenomena that occur. The theory of anomie and the new institutional theory serve as the analytical tools in this research to produce unique and comprehensive findings. The research findings affirm that there are two types of police in responding to institutional pressure: police who view institutional pressure as a whip to work harder, and police who feel pressured by that pressure. In addition to institutional pressure, police also face social pressure in the form of demands to meet public expectations, which include: (1) police as 'all- knowing gods'; (2) police as superheroes for the community; and (3) police acting as influencers. The disparity in access and resources among police officers in meeting institutional and societal expectations drives some members to experience ethical conflicts that result in violations of the code of ethics. In institutional theory, ethics should serve as a tool to regulate behavior. In reality, this is hindered by unequal access and resources for each member within an institution, in this case, police officers. As a result, police officers who do not have adequate access and resources are driven to commit ethical violations to respond to institutional and social pressures.